Influence of factors of the electric arc spraying process on the properties of coatings - Lopata, A.; Lopata, V.; Kachynska, I.; Zaboykina, N. (Problems of Tribology, 2024)
The article discusses primary (technological factors) relating to the technology and conditions of spraying and secondary ones, which are derived from technological factors affecting the structure formation and properties of coatings. The paper examines the influence of spraying distance, dispersion of sprayed particles, wire material, etc. on the properties of electric arc coatings. Summarizing the results of research on the influence of factors of the electric arc spraying process on the structure formation and properties of coatings, the parameters of the electric arc spraying process were established, the method of preparing the surface before spraying was selected, etc. method of processing sprayed coatings.